Structural properties of Nd-Ca-Mn-O bulk and thin film - Ishak, A. N.; Lim, K. P.; Lau, L. N.; Awang Kechik, M. M.; Chen, S. K.; Halim, S. A. (Malaysian Solid State Science and Technology Society, 2019)
Mixed-valent manganites perovskites have caught the eye of the researches over the past few years due to their captivating properties such as colossal magnetoresistance (CMR) effect and industrial purpose such as magnetic field sensing devices. In this study, Nd0.67Ca0.33MnO3 (NCMO) compounds have been synthesised into bulk by sol-gel method and fabricated into thin film via Pulsed Laser Deposition and were characterized by using X-ray diffraction (XRD) to study the structural properties of the compounds. Based on the XRD results, all bulk samples showed single phase formation with orthorhombic crystal structure but the thin film samples showed monoclinic structure type. The crystallite size of the samples increases as the sintering temperature increases because higher temperature promotes crystallite growth.